2005
DOI: 10.1038/sj.onc.1208872
|View full text |Cite
|
Sign up to set email alerts
|

UFD2a mediates the proteasomal turnover of p73 without promoting p73 ubiquitination

Abstract: p73 protein level is kept extremely low in mammalian cultured cells and its stability may be regulated by not only the ubiquitin/proteasome-dependent proteolysis but also through other unidentified mechanisms. Here, we found for the first time that p73 is physically as well as functionally associated with the U-box-type E3/E4 ubiquitin ligase UFD2a. The immunoprecipitation experiments demonstrated that this interaction is mediated by the COOH-terminal region of p73alpha containing SAM domain. During the cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 40 publications
1
51
1
1
Order By: Relevance
“…We found that NBL cell lines, NB-1 and NB-C201, carry a homozygous deletion at 1p36.2, and identified six genes within this region including DFF45/ICAD, PGD, CORT, UFD2a, KIF1B-b and PEX14 (Ohira et al, 2000). Among them, we have demonstrated that UFD2a promotes the proteasome-dependent degradation of p73 (Hosoda et al, 2005).…”
mentioning
confidence: 85%
“…We found that NBL cell lines, NB-1 and NB-C201, carry a homozygous deletion at 1p36.2, and identified six genes within this region including DFF45/ICAD, PGD, CORT, UFD2a, KIF1B-b and PEX14 (Ohira et al, 2000). Among them, we have demonstrated that UFD2a promotes the proteasome-dependent degradation of p73 (Hosoda et al, 2005).…”
mentioning
confidence: 85%
“…Furthermore, p73 proteins are sub-jected to post-translational modifications such as acetylation by acetyltransferase CBP/p300 (27) and phosphorylation by kinases including c-Abl (28 -30), JNK (31), p38 (32), and PKC␦ (33). Finally, p73 proteins can be targeted for ubiquitin-dependent and -independent proteasomal degradation by several E3 ligases, including the NEDD4-like ubiquitin ligase Itch (34), the F-box protein FBXO45 (35), the Ring finger domain ubiquitin ligases PIR2 and Pirh2 (36,37), and the U-box type E3/E4 ubiquitin ligase UFD2a (38). These results suggest that p73 expression is regulated by complex molecular signaling pathways.…”
mentioning
confidence: 99%
“…Data published previously have demonstrated that the Bax promoter can be activated upon TA-p73 overexpression [30,39,40]. Moreover, overexpression of p73 has been reported in various tumour types when compared with normal tissues [41][42][43][44][45] and has been reported to confer resistance to p53-mediated apoptosis induced by certain chemotherapeutic agents [46].…”
Section: Discussionmentioning
confidence: 99%
“…Positive stabilizers of TA-p73 protein and activity include MDM2 [50] -as in the case of p53 [51][52][53], YAP [54], and phosphorylation by PKC-d [55]. Conversely, TA-p73 activity can be negatively regulated by cyclin G [56], SUMO-1 [57], PIAS-1 [19] calpain I [58], UFD2a [39], PKA-Cb [30] and Itch [59]. Other identified binding partners to TA-p73 include HMGB1 and HMGB2, which stimulate or abrogate the binding of TA-p73 to p53 responsive elements (within the Bax promoter) in a cell specific manner [40].…”
Section: Discussionmentioning
confidence: 99%